Clipping of Complex Internal Cerebral Artery Terminus Aneurysm: 2‐Dimensional Operative Video. Issue 3 (September 2020) - Hendricks, Benjamin K.; Spetzler, Robert F.
Abstract : N/A: Internal carotid artery (ICA) bifurcation, or terminus, aneurysms are uncommon, and although they can be accessed with relative ease, clip occlusion of such aneurysms is often challenging due to the close proximity of basal forebrain perforator vessels. This patient had an incidentally discovered ICA terminus aneurysm and elected for microsurgical clipping. A modified orbitozygomatic approach was used to approach the aneurysm. The clipping was significantly complicated by the adherence and close proximity of the recurrent artery of Heubner to the aneurysm dome. Following successful dissection of the artery from the aneurysm dome and complete visualization of the aneurysm neck to avoid violation of perforator flow, successful clip occlusion of the aneurysm was achieved. The patient gave informed consent for surgery and video recording. Institutional review board approval was deemed unnecessary. Used with permission from Barrow Neurological Institute, Phoenix, Arizona .